Sustainability meets agile: Using Scrum to develop frugal innovations - Endres, Miro; Bican, Peter; Wöllner, Theresa (Journal of Cleaner Production, 2022)
With the climate crisis looming, innovations are no longer judged by their technical prowess alone but also on their sustainability. Frugal innovations have attracted significant attention in this regard. These user-friendly, cost-effective, and resource-efficient solutions of appropriate quality provide significant value to users and end customers and present attractive solutions to meet the current demands. Nevertheless, knowledge about the development of frugal solutions is scarce. Scrum is one of the most popular agile frameworks and is increasingly implemented in diverse companies' product development processes, although the relationship between Scrum and frugal innovation has not yet been investigated. Based on semi-structured expert interviews with Scrum practitioners, this paper provides the first insights into developing frugal innovations with Scrum. Interviewees generally considered Scrum's impact to be positive, and they named developing a user-friendly solution of appropriate quality as the frugal-innovation characteristic most benefited by applying Scrum. However, Scrum's impact was not explicit on the developed product's price-performance ratio, one of the variables to measure customer value. Therefore, this paper proposes integrating the user perspective into the Scrum process by identifying the actual users of the developed solution and by formally and regularly inviting them to sprint review meetings. To keep the development process efficient while addressing the identified stakeholder needs, organizations should work with fully dedicated, generalist Scrum teams that are knowledgeable on user experience. Additionally, Scrum team members should regularly share their insights gained with marketing departments to improve the effectiveness and appropriateness of pricing decisions. Companies can also address cost-effectiveness and sustainable resource efficiency by developing resource-efficient increments and by reusing existing components. Our study indicates that sustainability efforts, like reaching the UN Sustainable Development Goals, can profit from including agile frameworks in innovation activities.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Agile frameworks; Constrained-based innovation; Frugal innovation; Scrum; Sustainability; Inklusion